2004
DOI: 10.1038/sj.gene.6364112
|View full text |Cite
|
Sign up to set email alerts
|

CD14 promoter polymorphism −159C>T is associated with susceptibility to chronic Chlamydia pneumoniae infection in peripheral blood monocytes

Abstract: Chlamydia pneumoniae uses peripheral blood monocytes (PBMC) for systemic dissemination and has been linked to atherogenesis by inflammation mediated via TLR2/4 and CD14. We found 12.8% of 610 coronary artery disease (CAD) patients of Central European background to be chronically infected with C. pneumoniae based on the repeated detection of chlamydial DNA in PBMC. Among those the À159C4T CD14 promoter polymorphism was more frequent (OR 1.7, 95% CI 1.08-2.65, P ¼ 0.0224) than among C. pneumoniae-negative subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
(23 reference statements)
2
31
0
1
Order By: Relevance
“…This bears an interesting relationship to our findings in the present study, in which as-yetuncharacterized genetic susceptibility conferring sensitivity to experimental C trachomatis-induced arthritis was also associated with a relative lack of IFN␥ production locally. A comparable analogy can be seen in the significant associations observed between low TNF␣ secretion and a more chronic course of ReA in HLA-B27-positive patients, but that is not always the case (47,42). This also could represent the clinical parallel to that seen in the current study, in which relatively impaired host TNF␣ production was associated with the chronicity and severity of the experimental C trachomatis-induced arthritis.…”
Section: Host-microbe Interactions In Chlamydia-induced Arthritissupporting
confidence: 70%
See 1 more Smart Citation
“…This bears an interesting relationship to our findings in the present study, in which as-yetuncharacterized genetic susceptibility conferring sensitivity to experimental C trachomatis-induced arthritis was also associated with a relative lack of IFN␥ production locally. A comparable analogy can be seen in the significant associations observed between low TNF␣ secretion and a more chronic course of ReA in HLA-B27-positive patients, but that is not always the case (47,42). This also could represent the clinical parallel to that seen in the current study, in which relatively impaired host TNF␣ production was associated with the chronicity and severity of the experimental C trachomatis-induced arthritis.…”
Section: Host-microbe Interactions In Chlamydia-induced Arthritissupporting
confidence: 70%
“…Netea et al reported that Chlamydia pneumoniae stimulates IFN␥ synthesis through MyD88-dependent, Toll-like receptor 2 (TLR-2)-and TLR-4-independent induction of IL-18 release (46). Polymorphisms in CD14 may confer differential host responsiveness to chlamydia (47). Eng et al recently reported a CD14 promoter polymorphism associated with CD14 expression and Chlamydia-stimulated TNF␣ production (48).…”
Section: Host-microbe Interactions In Chlamydia-induced Arthritismentioning
confidence: 99%
“…3,4 Host genetic factors likely play an important role in this variability, and indeed, human genetic studies have shown associations between increased prevalence or severity of Chlamydia infection and certain human leukocyte antigen haplotypes [5][6][7][8] or polymorphisms in CD-14, tumor necrosis factor-a, or interleukin-10. [8][9][10] Although these reports show associations that are likely to be relevant, it is difficult to confirm their biological significance using human studies.…”
Section: Introductionmentioning
confidence: 99%
“…Host genetic factors appear to be important in determining the outcome of Chlamydia infections. It has been reported that the increased incidence of Chlamydia-induced chronic diseases, such as tubal infertility and scarring trachoma, is correlated with certain human leukocyte antigen (HLA) haplotypes and polymorphism of genes encoding interleukin-10 (IL-10), CD14, and tumor necrosis factor alpha (6,7,16,25,44,54). However, how these specific genes are involved in shaping the specific immune responses during Chlamydia infection in humans remains unclear.…”
mentioning
confidence: 99%